Lidar-Derived Decadal Change in Barrier Morphology: A Case Study of Waisanding, Taiwan - Hsien-Kuo Chang; Jin-Cheng Liou; Wen-Son Chiang; Wei-Wei Chen (Geosciences, 2024)
Barrier change is a complex process of evolution of coastal topography, which is related to the interaction of driving forces such as waves, tides and sea level rise (SLR) with beaches. The Waisanding Barrier (WSDB) in Taiwan has suffered from continuous beach erosion in recent decades. Some short-term studies have been carried out to understand the characteristics of the barrier change to provide a reference for future barrier protection. In this paper, the digital elevation model (DEM) measured by LiDAR (Light Detection and Ranging), over nearly two decades was used to analyze the morphological changes, the land area and volume. The changes in the morphology, including the whole shoreline, duneline height, width of forebeach and backbarrier, are investigated. The WSDB’s land area and land volume were analyzed to show a continuous decrease by a rate of −0.418 × 106 m2/year and −3.96 × 105 m3/year, respectively. The corresponding average land volume (LV) decrease in elevation can be estimated to be −0.0286 m/year. The changes in these features are discussed and relate to land subsidence, sea level rise and large waves induced by typhoons passing near WSDB.